1988
DOI: 10.1002/ijc.2910420625
|View full text |Cite
|
Sign up to set email alerts
|

Growth and metastasis of human tumors in nude mice following tumor‐cell inoculation into a vascularized polyurethane sponge matrix

Abstract: Growth and metastasis of human tumor cells in immunodeficient nude mice were improved when tumor cells were inoculated within a vascularized artificial polyurethane sponge matrix. The sponges had been implanted 7-10 days earlier and were vascularized at the time of cell injection. All cell lines tested, including colon carcinoma-derived lines from primary tumors (HT29, PT3 and PT4) or from liver metastasis (LM3), and a metastatic variant from a melanoma (MeWo-Met) grew in a high percentage (78-94%) of the inoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Polyester-polyurethane sponges (5×5 mm 2 ) (Vitaform Ltd, Manchester, UK) containing heatkilled Listeria monocytogenes were implanted s.c. in C57BL/6 mice [44]. After 4 days mice were treated with 200 µg CD28SA or PBS i.p.. On day 7 sponges were recovered, cells were washed out several times with BSS/BSA and stained for Foxp3 and IL-10 via IL-10 Secretion Assay.…”
Section: Methodsmentioning
confidence: 99%
“…Polyester-polyurethane sponges (5×5 mm 2 ) (Vitaform Ltd, Manchester, UK) containing heatkilled Listeria monocytogenes were implanted s.c. in C57BL/6 mice [44]. After 4 days mice were treated with 200 µg CD28SA or PBS i.p.. On day 7 sponges were recovered, cells were washed out several times with BSS/BSA and stained for Foxp3 and IL-10 via IL-10 Secretion Assay.…”
Section: Methodsmentioning
confidence: 99%
“…The growth and metastasis of human tumors in nude mice following tumor-cell inoculation into a vascularized polyurethane sponge matrix have been studied [97]. The sponge material induces a nonspecific inflammatory reaction, which mediates angiogenesis and connective tissue infiltration.…”
Section: Tumor Growth In Vascularized Subcutaneous Polyurethane Spongesmentioning
confidence: 99%
“…Sponge implants have been previously employed for in vivo characterization of different facets of the function of newly formed or developing blood vessels, including their pharmacological reactivity (3), role in tumor growth and metastasis (43), and responsiveness to angiogenic agents (2). Recently, it has been shown that several angiogenic peptides, including VEGF and bFGF, can interfere with the expression of endothelial glycoproteins on proliferating endothelial cells (18,31).…”
Section: Sponge Implantationmentioning
confidence: 99%